PEMANFAATAN TEKNOLOGI SEBAGAI MEDIA PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 - I Gd. Dedy Diana Putra (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2022)
Along with the turmoil of phenomena that occur in the world, the Covid 19 pandemic is one of the causes of turmoil in the world. For this reason, humans must dynamically follow the changes that occur, it aims to avoid the stagnation of the world's life cycle. Technology is a solution to the outbreak of Covid 19 that has surfaced so that it has an impact on systematic changes in the world, one of which is the education system.This paper aims to provide an overview of the important role of technology in the field of education during the Covid 19 Pandemic. To produce valid and reliable data, this paper is qualitatively styled using descriptive analysis methods. So that the writing results are logical, objective and empirical. The series of steps carried out are reducing data, displaying data, verifying data, and interpreting research data, which were obtained through the literature study method.Technology contributes greatly to fundamental changes in the structure, operation, and management of education and learning systems. Utilization of technology can be felt in the learning process such as teaching presentations, access to information (e-learning) or learning development. The use of technology in online learning is a bridge that has an impact on major changes in the learning process. Technology will give hegemony to students and educators to act and process more advanced with the use of technology. Technology-based learning tends to lead students to be more active in finding information in supporting the learning process to print superior, creative, innovative resources and be able to compete in global developments.Keywords: Utilization of Technology, Learning Media, Covid 19 Pandemic